Efficacy and Cost Analysis of Food-Based Interventions to Treat Children With Undernutrition: A Systematic Review - Helmyati, Siti; Kusuma, Mutiara Tirta Prabandari Lintang; Hariawan, Muhammad Hafizh; Lukito, Widjaja; Rachmawati, Yuliana Novita; Rosilia, Gifani; Renita, Renita; Syarifa, Cut Alima (Malaysian Journal of Medical Sciences, 2026)
Background: Mitigating malnutrition is one of the Sustainable Development Goals that countries commit to achieve. This study aimed to determine the effects of food for special medical purposes (FSMPs) on nutrition status and other outcomes on children under five with undernutrition. Methods: This review summarised the findings of 15 articles. The articles were experimental, compared intervention with a control group, published between 2012 and 2022, and directly or indirectly measured children’s nutrition status. The risk of bias and quality of the articles were assessed using the Joanna Briggs Institute critical appraisal tool. Results: Three types of FSMPs were identified as treatment for children with malnutrition. Ready-to-use supplementary foods improved child growth in terms of weight gain. Ready-to-use therapeutic foods mostly resulted in higher recovery rates. Oral nutrition supplements yielded significant increases in body weight and height. However, the economic value of administering FSMPs on children with malnutrition was not determined because of data scarcity. Conclusion: FSMP provision to treat malnutrition in children resulted in better growth outcomes. However, further studies are needed to measure the health and economic effects of FSMPs.